Differential clinic in children infected by SARS-CoV-2, traceability of contacts and cost-effectiveness of diagnostic tests: Cross-sectional observational study - Antia Fiel-Ozores; María Luisa González-Durán; Reyes Novoa-Carballal; María del Mar Portugués-de la Red; Isabel Fernández-Pinilla; Jorge Julio Cabrera-Alvargonzález; Cristina Martínez-Reglero; Sonia Rey-Cao; Ana Concheiro-Guisán (Elsevier, 2021)
Introduction: Given the possible coexistence of infection by the SARS-CoV-2 with other seasonal infections, the aim is to identify differential symptoms. The role of children in intrafamily contagion and the sensitivity of reverse transcriptase polymerase chain reaction (RT-PCR) in an area with low community transmission has been studied. Material and methods: Cross-sectional observational study. Patients between 0-15 years studied by RT-PCR technique due to clinical suspicion of infection by SARS-CoV-2 virus in the months of March-May 2020. Survey on symptoms and contacts. Determination of Anti-SARS-CoV-2 antibodies at least 21 days after the RT-PCR test. Results: 126 patients were included, 33 with confirmed infection and age mean 8.4 years (95% CI 6.8-10.5) higher than not infected. Fever was the most common and with greater sensitivity. The differences found were a greater frequency of anosmia (P = .029) and headache (P = .009) among children infected with a specificity of 96.7% and 81.5% respectively. There were no differences in the duration of the symptoms. 81.8% of those infected were probably infected in the nucleus 85.2% by a parent who worked outside the home. The sensitivity of RT-PCR was 70.9% and its negative predictive value 91.1%. Conclusions: The clinical picture is nonspecific and the symptoms more specific difficult to detect in younger children. Children had a reduced role in the intrafamily transmission. The sensitivity of RT-PCR could be related to a less contagiousness in children after one week of infection. Resumen: Introducción: Ante la posible coexistencia de la infección por el virus SARS-CoV-2 con otras infecciones estacionales, se pretende identificar síntomas diferenciales. Se ha estudiado el papel de los niños en el contagio intrafamiliar y la sensibilidad de la reacción en cadena de la polimerasa con transcriptasa inversa (RT-PCR) en un área con baja transmisión comunitaria. Material y métodos: Estudio observacional transversal. Pacientes entre 0-15 años estudiados por técnica RT-PCR por sospecha clínica de infección por virus SARS-CoV-2 en los meses de marzo-mayo del 2020. Encuesta sobre síntomas y contactos. Determinación de anticuerpos anti-SARS-CoV-2 al menos 21 días después del test RT- PCR. Resultados: Se incluyó a 126 pacientes, 33 con infección confirmada y edad media 8,4 años (IC del 95%, 6,8-10,0) superior a los no infectados. La fiebre fue el síntoma más común y con mayor sensibilidad. Las diferencias encontradas fueron una mayor frecuencia de anosmia (p = 0,029) y cefalea (p = 0,009) entre los niños infectados con una especificidad del 96,7 y el 81,5% respectivamente. No hubo diferencias en la duración de los síntomas.Un 81,8% de los infectados fue probablemente contagiado en el núcleo familiar, en un 85,2% por un progenitor que trabajaba fuera del hogar. La sensibilidad de RT-PCR fue 70,9% y su valor predictivo negativo 91,1%. Conclusiones: El cuadro clínico es inespecífico y los síntomas más específicos difíciles de detectar en niños más pequeños. Los niños tuvieron un papel reducido en la transmisión intrafamiliar. La sensibilidad de la RT-PCR podría estar relacionada con una menor contagiosidad infantil tras una semana de infección.